Economic Transition and Labor Market Reform in China - Ma, Xinxin (Springer Singapore, 2018)
This book empirically investigates the changes in labor market structure accompanying the labor market reform in China by focusing on the labor market segmentation problems from the 1980s to 2013. The book also aims to examine the effect of labor policy reforms on individual, household and enterprise behavior, including the causes and consequences of labor market reform in China, particularly the influences of labor policy reforms on labor market performance. Offering valuable insights into the changing structure of the Chinese economy, this book will be of interest to scholars, activists, and economists. Xinxin Ma is Associate Professor at the Department of Comparative and World Economics, Institute of Economic Research, Hitotsubashi University, Japan.